Renal disease in pregnancy - Davison, John M. (RCOG Press, 2008)
The 54th RCOG Study Group brought together a range of experts from across many disciplines to examine the most up-to-date evidence on all aspects of diagnosis and management in women with renal problems before, during and after pregnancy. This book presents the findings of the Study Group, describing many of the issues likely to be faced in clinical practice and providing valuable information for all healthcare professionals working in this field. General principles for optimal management are clearly defined and separate chapters are devoted to specific disease entities and/or clinical situations. Many controversial areas - such as management of hypertension, diagnosis of pre-eclampsia, assisted conception, rationalisation of the many medications used in nephrology practice, renal biopsy, surgical emergencies, patient input and responsibilities - are carefully considered.